First record of gastroliths associated with elasmosaur remains from La Colonia Formation (CampanianeMaastrichtian), Chubut, Patagonia Argentina, with comments on the probable depositional palaeoenvironment of the source of the gastroliths - O'gorman, Jose Patricio (2013)
A gastrolith set, comprising 197 elements, associated with an indeterminate elasmosaurid plesiosaur collected from the CampanianeMaastrichtian La Colonia Formation, Chubut, Argentina, is described. Most of the gastroliths are discoidal (41.9%) or spheroidal (34.8%), with a mean Maximum Projection Sphericity Index value of 0.69 and a mean OP Index value of 0.74. The values of these indices are compared with those recorded for gastroliths associated with other Upper Cretaceous elasmosaurids to see if patterns with palaeobiological relevance are evident. The mean values of the Maximum Projection Sphericity Index and the Oblate-Prolate Index allow us to infer a fluvial or estuarine origin for all the elasmosaurid gastroliths for which these indices have been calculated. This inference is palaeobiologically informative because it indicates that at least some Upper Cretaceous elasmosaurs entered into estuarine (or fluvial) environments. It also helps explain the interesting vertebrate assemblage of the Allen and La Colonia formations where a rich continental fauna is recorded but elasmosaurids and polycotylids are the only well represented vertebrates with marine affinities.